Medical Rehabilitation of Patients Who Have Undergone Surgical Treatment of Gynecological Diseases: a Scientometric Analysis of Studies - Denis V. Kovlen; Igor S. Zakharov; Elena F. Kodrina; Alexander A. Bezmenko; Nikita A. Trigubchuk (Вестник восстановительной медицины)
INTRODUCTION. Surgical treatment of gynecological diseases in patients of reproductive age is often associated with a number of complications. These problems initiate a discussion regarding the implementation of measures aimed at restoring the impaired functions of the genitals.